2009
DOI: 10.1002/esp.1751
|View full text |Cite
|
Sign up to set email alerts
|

Hydroclimatic and channel snowpack controls over suspended sediment and grain size transport in a High Arctic catchment

Abstract: Temporal variability in suspended sediment delivery processes was studied during three seasons in a 7·9 km 2 catchment at Cape Bounty, Melville Island, Nunavut in the Canadian High Arctic. Discharge was controlled primarily by the magnitude of snowmelt, with limited inputs from ground ice melt and precipitation. Years with greater snowpack non-linearly increased sediment yield and resulted in seasonal counter-clockwise hysteresis, while a year with low snowpack resulted in reduced sediment yield and clockwise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 43 publications
2
53
0
Order By: Relevance
“…1). As part of a long-term research program (the Cape Bounty Arctic Watershed Observatory), hydrological, limnological, and sedimentary processes have been investigated and monitored in two adjacent lakes and watershed systems since 2003 (Lamoureux et al 2006;Cockburn and Lamoureux 2008a, b;Dugan et al 2009;McDonald and Lamoureux 2009;Laurin 2010;Pautler et al 2010;Lewis et al 2011;Stewart and Lamoureux 2011). The East and West lakes (unofficial names) have similar morphologies: both are *1.5 km 2 , and maximum depths are 30 and 34 m, respectively.…”
Section: Study Sitementioning
confidence: 98%
“…1). As part of a long-term research program (the Cape Bounty Arctic Watershed Observatory), hydrological, limnological, and sedimentary processes have been investigated and monitored in two adjacent lakes and watershed systems since 2003 (Lamoureux et al 2006;Cockburn and Lamoureux 2008a, b;Dugan et al 2009;McDonald and Lamoureux 2009;Laurin 2010;Pautler et al 2010;Lewis et al 2011;Stewart and Lamoureux 2011). The East and West lakes (unofficial names) have similar morphologies: both are *1.5 km 2 , and maximum depths are 30 and 34 m, respectively.…”
Section: Study Sitementioning
confidence: 98%
“…A few longer studies looking at multiple time scales have shown considerable temporal variation in sediment patterns. McDonald and Lamoureux [15] found significant temporal variation in suspended sediment transport in High Arctic catchments that was linked to snow melt. Rodriguez-Blanco et al [6] found for agricultural basins in Spain that at the event scale sediment peaked before discharge, at the seasonal time scale sediment yield decreased through the season, and at the annual scale yield was linked to the percentage of the year that large events occurred.…”
Section: Introductionmentioning
confidence: 99%
“…However, much of this work has been focused on individual discharge events [10][11][12], or has been in predominately agricultural areas [4,6,7,[11][12][13], in small hillslope plots [11] or in areas with drastically different physiographic and climatic regimes [7,14,15]. A few longer studies looking at multiple time scales have shown considerable temporal variation in sediment patterns.…”
Section: Introductionmentioning
confidence: 99%
“…In spring, the rise in solar radiation and above-freezing air temperatures rapidly melt the snow cover and result in an increase in water flow and transport (Hudon et al 1996). However, during the freshet flood, a relatively low turbidity indicates that transport of TSS likely remains low because some channels stay armored with ice and snow and soils are still frozen, as observed in other catchments in the Arctic and Subarctic (McDonald and Lamoureux 2009). …”
Section: Turbidity and Sediment Transportmentioning
confidence: 97%